Perfil nutricional, sarcopenia e capacidade funcional de pacientes em um centro oncológico especializado no município de Fortaleza - CE - Nascimento, Bruna Pereira do (2023)
Currently, the growing incidence and prevalence of the number of cancer cases represent a serious public health problem in Brazil and in the world, where the main nutritional problem and probably the most impactful on the prognosis is the loss of muscle mass. The aim of this study was to evaluate sarcopenia, nutritional profile and functional capacity of cancer patients treated at an oncology center in the city of Fortaleza - Ceará. This was a cohort, observational, prospective and longitudinal study, carried out from September 2021 to October 2022. The sample consisted of 63 patients, clinical and treatment data were collected from electronic medical records. Sarcopenia was screened using the SARC-CalF score, muscle strength was assessed using the sit-up test, and functional capacity was assessed using the Eastern Cooperative Oncology Group Performance Status (PS-ECOG) scale. Soon after, the anthropometric evaluation was performed. The Two-Way ANOVA test was applied to assess the number of cases in the groups with and without risk of sarcopenia. Pearson's chi-square test was applied to compare the probable influence between the clinical variables of the nutritional profile and functional capacity with the group of sarcopenic versus non-sarcopenic individuals. Significant differences were considered with a 95% confidence interval (p < 0.05). The results showed patients with a higher prevalence of primary urologic and breast cancers undergoing chemotherapy. And among the gastrointestinal symptoms, there was a higher prevalence of lack of appetite in 40% (n=25) and nausea in 29% (n=18) of the patients. Regarding the nutritional status, excess weight in individuals was highlighted. Functional capacity was preserved, but the number of individuals at risk of sarcopenia increased from 17 to 20 (p < 0.001) and 88% of those patients who scored positively in the screening were unable to perform the stand-up and sit-down test in a satisfactory time < 15 seconds. Comparative analyzes were performed with the groups without risk and with risk of sarcopenia at T1 and significances (p<0.05) were observed in variables such as BMI, age, types of treatments and performance status. Based on these results, we also aimed at improving care planning for patients by creating a booklet for managing sarcopenia. Thus, it was possible to assess sarcopenia, clinical-nutritional profile and functional capacity of cancer patients. It is worth noting that individuals with an increased risk of sarcopenia were mostly eutrophic individuals, which indicates that BMI was not reliable for assessing muscle reserves.